Tannin–Mn coordination polymer coated carbon quantum dots nanocomposite for fluorescence and magnetic resonance bimodal imaging - Xu, Weibing; Zhang, Jia; Yang, Zhijie; Zhao, Minzhi; Long, Haitao; Wu, Qingfeng; Nian, Fang (Journal of materials science. Materials in medicine, 2022)
The MR/FI bimodal imaging has attracted widely studied due to combining the advantages of MRI and FI can bridge gaps in sensitivity and depth between these two modalities. Herein, a novel MR/FI bimodal imaging probe is facile fabricated by coating the Mn-phenolic coordination polymer on the surface of the carbon quantum dots. The structure of the as-prepared nanocomposite probe is carefully validated via SEM, TEM, and XPS. The content of Mn 2+ is calculated through the EDS and TGA. The quantum yield (QY) and emission wavelength of the probe are about 7.24% and 490 nm, respectively. The longitudinal r1 value (2.43 mM −1 s −1 ) with low r2/r1 (4.45) of the probe is obtained. Subsequently, fluorescence and MR imaging are performed. The metabolic pathways in vivo are inferred by studying the bio-distribution of the probe in major organs. Thus, these results indicate that probe would be an excellent dual-modal imaging probe for enhanced MR imaging and fluorescence imaging. MR/FI bimodal imaging probe is built via in-situ coated Mn-phenolic coordination polymer on the surface of the carbon quantum dots. The in vitro and vivo image property of the probe is evaluated.